2014
DOI: 10.1089/ten.tec.2013.0147
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Simple Alternative to Create Nanofibrillar Matrices of Interest for Tissue Engineering

Abstract: Synthetic analogs to natural extracellular matrix (ECM) at the nanometer level are of great potential for regenerative medicine. This study introduces a novel and simple method to produce polymer nanofibers and evaluates the properties of the resulting structures, as well as their suitability to support cells and their potential interest for bone and vascular applications. The devised approach diffracts a polymer solution by means of a spraying apparatus and of an airstream as sole driving force. The resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Their inherent small fibre diameters and arbitrary fibre deposition reduces the pore size, thus limits cell infiltration and possibly ECM production [42]. Jet-sprayed scaffolds also have small fibre diameters, but provide a high porosity that enhances cell infiltration, ECM production and osteogenic differentiation [43,44]. However, there is little control over fibre diameter and fibre deposition [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their inherent small fibre diameters and arbitrary fibre deposition reduces the pore size, thus limits cell infiltration and possibly ECM production [42]. Jet-sprayed scaffolds also have small fibre diameters, but provide a high porosity that enhances cell infiltration, ECM production and osteogenic differentiation [43,44]. However, there is little control over fibre diameter and fibre deposition [48].…”
Section: Discussionmentioning
confidence: 99%
“…PCL has been extensively used for bone tissue engineering due to its inherent good mechanical properties, biocompatibility and low degradation rate [41,43,44]. Our group has already demonstrated that melt electrospun PCL scaffolds are suitable to engineer bone constructs to study species-specific mechanisms in vivo [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The fibre networks produced typically exhibit more open inter-fibre porosity than electrospun mats [7,8]. A range of materials have been successfully processed to fibres by SBS to date, including polymers [2,3], composites [9,10], ceramic fibres either by incorporating inorganic components in a matrix followed by burn-off of the organic matrix and sintering [11][12][13], and those derived by sol-gel precursors and subsequent calcination [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many studies to explore the compatibility of airbrush spraying with a number of polymers for production of nanofibers or thin films, there have been only a few studies on the compatibility of airbrush spraying with hydrogels. The possibility of in situ deposition of thermoresponsive hydrogels holds promise for a host of applications ranging from the treatment of burn wounds and ulcers to the regeneration of bone and cartilage tissue defects.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, researchers have explored the compatibility of spraying with a number of cell types, including epithelial and smooth muscle cells for coating tissueengineered constructs like trachea or bronchi, 16 keratinocytes and bovine dermal fibroblasts for chronic or burn wound healing, 17,18 and chondrocytes for cartilage repair. 14 Although there have been many studies to explore the compatibility of airbrush spraying with a number of polymers for production of nanofibers 13,[19][20][21][22][23][24][25][26][27] or thin films, [28][29][30] there have been only a few studies 31,32 on the compatibility of airbrush spraying with hydrogels. The possibility of in situ deposition of thermoresponsive hydrogels holds promise for a host of applications ranging from the treatment of burn wounds and ulcers to the regeneration of bone and cartilage tissue defects.…”
Section: Introductionmentioning
confidence: 99%